Two-dimensional device modeling of CH3NH3PbI3 based planar heterojunction perovskite solar cells. (January 2016) - Zhou, Qian; Jiao, Debao; Fu, Kailiang; Wu, Xiaojie; Chen, Yongsheng; Lu, Jingxiao; Yang, Shi-e
Highlights: The CH3 NH3 PbI3 based planar heterojunction perovskite solar cells is simulated using a 2D model. The optical and electrical responses are coupled in calculation. An optimized absorber thickness of 200–300 nm is gained for L n greater than 250 nm. A double HTMs design is proposed to match the valence bands between absorber and HTM. The effect of dielectric constant is studied. Abstract: Recently, organo–metal halide perovskites have attracted much attention of the scientific community relating to their successful application in the absorber layer of low-cost solar cells. However, enough is known about the material and device properties, to realize that much remains to be learned. In this study, a two-dimensional modeling of planar heterojunction perovskite solar cells was performed combining the optical and electrical responses to reveal the impact of the carrier diffusion length, the relative permittivity of absorber layer and the valence band offset of absorber/hole transport material (HTM). Simulation results presented a great dependence of power conversion efficiency (PCE) on the carrier diffusion length of perovskite layer. Meanwhile, to achieve high PCE, the frequency depended dielectric constant should not exceeded 40 and the double HTMs design was very effective to match the valence bands between the absorber and HTM.